INFLUENCE OF SEASONS AND PLANT PARTS ON THE ESSENTIAL OIL COMPOSITION OF THE ENDEMIC SPECIES ARISTOLOCHIA KRISAGATHRA SIVARAJAN AND PRADEEP - Murali, Soumya; R., Rashmi T.; S., Francis M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Aristolochia krisagathra, a species endemic to the Western Ghats of India is found closely allied to two other species native to India, A. indica and A. tagala. The plant is medicinally useful and hence may harbor important phytochemical constituents. The phytochemical studies on this plant are less. Hence, the objective of the research was to analyse the oil composition of this endemic plant considering the seasons and plant parts. Methods: The essential oil analyses of both the leaf and stem oil of the plant was carried out in three different periods, pre-monsoon, monsoon and post-monsoon to analyse the major compounds present and the effect of seasons on the oil composition. Oil extraction of the shade dried leaves and stem were done in a clevenger type apparatus. 4 h of hydro distillation was done and the oil samples were analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). Results: The stem oil yield was higher than leaves and the oil colour of the leaves and stem varied. The results showed the predominance of sesquiterpenes. Diterpenes were completely absent in the stem oil in all the three seasons but was present in leaf oil in small concentrations. The oil yield from stem was higher than leaves. The major compound in the leaf and stem oil varied. Major compound in the pre-monsoon and post-monsoon remained the same, copaene in the leaf and alloaromadendrene in the stem. The major compound in the monsoon period was delta-cadinene in leaf and spathulenol in stem. Caryophyllene, the sesquiterpene hydrocarbon, was present in both the stem and leaf oil irrespective of the seasons studied. Conclusion: The study showed that the plant parts and seasons are important factors affecting the oil composition. Hence while collecting medicinal plants and their oils for various bioactivities, these factors need to be considered.